You Can Teach an Old Drug New Tricks. Issue 4 (July 2020) - Perry, M. Scott
Fenfluramine for Treatment-Resistant Seizures in Patients With Dravet Syndrome Receiving Stiripentol-Inclusive Regimens: A Randomized Clinical Trial Nabbout R, Mistry A, Zuberi S, et al. JAMA Neurol . 2020;77(3):300-308. doi:10.1001/jamaneurol.2019.4113 . Importance: Fenfluramine treatment may reduce monthly convulsive seizure frequency in patients with Dravet syndrome who have poor seizure control with their current stiripentol-containing antiepileptic drug regimens. Objective: To determine whether fenfluramine reduced monthly convulsive seizure frequency relative to placebo in patients with Dravet syndrome who were taking stiripentol-inclusive regimens. Design, Setting, and Participants: This double-blind, placebo-controlled, parallel-group randomized clinical trial was conducted in multiple centers. Eligible patients were children aged 2 to 18 years with a confirmed clinical diagnosis of Dravet syndrome who were receiving stable, stiripentol-inclusive antiepileptic drug regimens. Interventions: Patients with 6 or more convulsive seizures during the 6-week baseline period were randomly assigned to receive fenfluramine, 0.4 mg/kg/d (maximum, 17 mg/d), or a placebo. After titration (3 weeks), patients' assigned dosages were maintained for 12 additional weeks. Caregivers recorded seizures via a daily electronic diary. Main Outcomes and Measures: The primary efficacy end point was the change in mean monthly convulsive seizure frequency between fenfluramine and placebo during the combined titration and maintenance periods relative to baseline. Results: A total of 115 eligible patients were identified; of these, 87 patients (mean [standard deviation], age 9.1 [4.8] years; 50 [57%] male patients; mean baseline frequency of seizures, approximately 25 convulsive seizures per month) were enrolled and randomized to fenfluramine, 0.4 mg/kg/d (n = 43), or placebo (n = 44). Patients treated with fenfluramine achieved a 54.0% (95% CI, 35.6%-67.2%; P < .001) greater reduction in mean monthly convulsive seizure frequency than those receiving the placebo. With fenfluramine, 54% of patients demonstrated a clinically meaningful (≥50%) reduction in monthly convulsive seizure frequency versus 5% with placebo ( P < .001). The median (range) longest seizure-free interval was 22 (3.0-105.0) days with fenfluramine and 13 (1.0-40.0) days with placebo ( P = .004). The most common adverse events were decreased appetite (19 [44%] patients taking fenfluramine vs 5 [11%] taking placebo), fatigue (11 [26%] vs 2 [5%]), diarrhea (10 [23%] vs 3 [7%]), and pyrexia (11 [26%] vs 4 [9%]). Cardiac monitoring demonstrated no clinical or echocardiographic evidence of valvular heart disease or pulmonary arterial hypertension. Conclusions and Relevance: Fenfluramine demonstrated significant improvements in monthly convulsive seizure frequency in patients with Dravet syndrome whose conditions were insufficiently controlled with stiripentol-inclusive antiepileptic drug regimens. Fenfluramine was generally well tolerated. Fenfluramine may represent a new treatment option for Dravet syndrome. Fenfluramine Hydrochloride for the Treatment of Seizures in Dravet Syndrome: A Randomised, Double-Blind, Placebo-Controlled Trial Lagae L, Sullivan J, Knupp K, et al. Lancet . 2019;394(10216):2243-2254. doi:10.1016/s0140-6736(19)32500-0 Background: Dravet syndrome is a rare, treatment-resistant developmental epileptic encephalopathy characterized by multiple types of frequent, disabling seizures. Fenfluramine has been reported to have antiseizure activity in observational studies of photosensitive epilepsy and Dravet syndrome. The aim of the present study was to assess the efficacy and safety of fenfluramine in patients with Dravet syndrome. Methods: In this randomized, double-blind, placebo-controlled clinical trial, we enrolled children and young adults with Dravet syndrome. After a 6-week observation period to establish baseline monthly convulsive seizure frequency (MCSF; convulsive seizures were defined as hemiclonic, tonic, clonic, tonic–atonic, generalized tonic–clonic, and focal with clearly observable motor signs), patients were randomly assigned through an interactive web response system in a 1:1:1 ratio to placebo, fenfluramine 0.2 mg/kg/d, or fenfluramine 0.7 mg/kg/d, added to existing antiepileptic agents for 14 weeks. The primary outcome was the change in mean monthly frequency of convulsive seizures during the treatment period compared with baseline in the 0.7 mg/kg/d group versus placebo; 0.2 mg/kg/d versus placebo was assessed as a key secondary outcome. Analysis was by modified intention to treat. Safety analyses included all participants who received at least one dose of study medication. This trial is registered withClinicalTrials.gov with 2 identical protocols NCT02682927 and NCT02826863. Findings: Between January 15, 2016, and August 14, 2017, we assessed 173 patients, of whom 119 patients (mean age 9·0 years, 64 [54%] male) were randomly assigned to receive fenfluramine 0.2 mg/kg/d (39), fenfluramine 0.7 mg/kg/d (40), or placebo (40). During treatment, the median reduction in seizure frequency was 74.9% in the fenfluramine 0.7 mg/kg group (from median 20.7 seizures per 28 days to 4.7 seizures per 28 days), 42.3% in the fenfluramine 0.2 mg/kg group (from median 17.5 seizures per 28 days to 12.6 per 28 days), and 19.2% in the placebo group (from median 27.3 per 28 days to 22.0 per 28 days). The study met its primary efficacy end point, with fenfluramine 0.7 mg/kg/d showing a 62.3% greater reduction in mean MCSF compared with placebo (95% CI, 47.7-72·8, P < .0001); fenfluramine 0.2 mg/kg/d showed a 32.4% reduction in mean MCSF compared with placebo (95% CI, 6.2-52.3, P = .0209). The most common adverse events (occurring in at least 10% of patients and more frequently in the fenfluramine groups) were decreased appetite, diarrhea, fatigue, lethargy, somnolence, and decreased weight. Echocardiographic examinations revealed valve function within the normal physiological range in all patients during the trial and no signs of pulmonary arterial hypertension. Interpretation: In Dravet syndrome, fenfluramine provided significantly greater reduction in convulsive seizure frequency compared with placebo and was generally well tolerated, with no observed valvular heart disease or pulmonary arterial hypertension. Fenfluramine could be an important new treatment option for patients with Dravet syndrome. Funding: Zogenix.